2023
DOI: 10.1021/acsaem.3c01042
|View full text |Cite
|
Sign up to set email alerts
|

Triboelectric Nanogenerator with a Rotational Freestanding Mode for Multi-directional Vibration Energy Harvesting

Abstract: Harvesting the vibration energy commonly found in engines, air compressors, and other machines is of great significance for energy recovery and reutilization. However, due to the small vibration amplitude and non-single vibration directions, the conventional vibration energy harvesters based on triboelectric nanogenerators (TENGs) have a low efficiency. In this work, we proposed a TENG with a rotational freestanding mode (RFM-TENG), which can effectively harvest the mechanical vibration energy with a small amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
1
0
Order By: Relevance
“…Figure e shows the FFT analysis of vertical and horizontal TENG output voltage signals, where both can accurately indicate the 25 Hz main vibration frequency of the air compressor. In summary, Table S1 shows a comparison between the TFTD-TENG and other previous studies, ,, ,, the TFTD-TENG exhibits relatively higher and unique multidirectional output performance.…”
Section: Resultsmentioning
confidence: 93%
“…Figure e shows the FFT analysis of vertical and horizontal TENG output voltage signals, where both can accurately indicate the 25 Hz main vibration frequency of the air compressor. In summary, Table S1 shows a comparison between the TFTD-TENG and other previous studies, ,, ,, the TFTD-TENG exhibits relatively higher and unique multidirectional output performance.…”
Section: Resultsmentioning
confidence: 93%
“…Chen et al fabricated an R-TENG based on a double friction layer rotating disc structure, producing a peak power density of 1.36 W/m 2 at a rotation speed of 600 rpm [ 12 ]. Generally, these disc-type R-TENGs generate high output power due to their large contact area and effective triboelectrification but require a strong driving force to overcome the sliding friction, which typically results in severe abrasion of the triboelectric layers [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that TENG has become a versatile and efficient energy-harvesting and self-powered sensing technology with applications ranging from small-scale portable electronics to large-scale blue energy harvesting [ 30 , 31 , 32 , 33 , 34 ]. TENG has the advantages of low cost, light weight, simple structure, strong environmental compatibility, wide material selection, etc., showing obvious advantages in the field of self-powered vibration sensing technology [ 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. In this paper, a vibration sensor based on ball TENG (B-TENG) was designed for marine pipelines condition monitoring.…”
Section: Introductionmentioning
confidence: 99%